The future of US-Turkish relations under the Joe Biden administration - أبو شومر, محمد; محمد معن ديوب; ميساء اسبر (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study deals with the issue of Turkish-American relations and their future under the administration of US President Joe Biden (2021-2024). The study discussed the emergence and history of Turkish-American relations since the era of the Ottoman Empire. It also addressed the most prominent stages of the development of relations between the two parties during the period 2000-2022, where That period witnessed many geopolitical developments at the international and regional levels, and the study reached important results related to the complexity of US-Turkish relations under the administration of Joe Biden. Temporary tactical differences constitute a distinctive feature in the relations between the two parties, but those temporary differences did not lead to Dismantling the strategic alliance between Ankara and Washington, where the repercussions of the Russian-Ukrainian war formed an opportunity for the development and rapprochement of relations between the two parties. At its conclusion, the study presents three basic scenarios that explain the future of US-Turkish relations under the Joe Biden administration.